Design of a H2O2‐generating P450SPα fusion protein for high yield fatty acid conversion. (22nd November 2022) - Giuriato, Daniele; Correddu, Danilo; Catucci, Gianluca; Di Nardo, Giovanna; Bolchi, Cristiano; Pallavicini, Marco; Gilardi, Gianfranco
Abstract: Sphingomonas paucimobilis' P450SPα (CYP152B1) is a good candidate as industrial biocatalyst. This enzyme is able to use hydrogen peroxide as unique cofactor to catalyze the fatty acids conversion to α‐hydroxy fatty acids, thus avoiding the use of expensive electron‐donor(s) and redox partner(s). Nevertheless, the toxicity of exogenous H2 O2 toward proteins and cells often results in the failure of the reaction scale‐up when it is directly added as co‐substrate. In order to bypass this problem, we designed a H2 O2 self‐producing enzyme by fusing the P450SPα to the monomeric sarcosine oxidase (MSOX), as H2 O2 donor system, in a unique polypeptide chain, obtaining the P450SPα ‐polyG‐MSOX fusion protein. The purified P450SPα ‐polyG‐MSOX protein displayed high purity (A417 /A280  = 0.6) and H2 O2 ‐tolerance ( k decay  = 0.0021 ± 0.000055 min −1 ; ΔA417  = 0.018 ± 0.001) as well as good thermal stability ( T m : 59.3 ± 0.3°C and 63.2 ± 0.02°C for P450SPα and MSOX domains, respectively). The data show how the catalytic interplay between the two domains can be finely regulated by using 500 mM sarcosine as sacrificial substrate to generate H2 O2 . Indeed, the fusion protein resulted in a high conversion yield toward fat waste biomass‐representative fatty acids, that is, lauric acid (TON = 6, 800 compared to the isolated P450SPα TON = 2, 307); myristic acid (TON = 6, 750); and palmitic acid (TON = 1, 962).